Four-Parameter Shifts Control Chaos and Lead to Physical Behaviour in a Dual-Ring Erbium-Doped Fiber Laser. Issue 1 (1st January 2022) - Yan, Senlin
Abstract: We study on a four-parameter shift (FPS) chaos-control method to obtain control of a chaotic dual-ring erbium-doped fiber laser and lead to physics behaviours of two laser rings. To control two chaotic laser rings, the pump parameters and gain parameters of dual-ring lasers are modulated simultaneously by four shift digital signals. It is found that controls of the two chaotic laser rings are realized and physics behaviours of two laser rings can be guided by FPS. As a result, chaos is led to two periodic behaviours. And physics movements of dual-ring lasers are guided to period-4, period-5, period-6, period-7, and some high-order-period. The obtained results have a large helpfulness for people' study of control of dynamics system, control of chaos, optic control science, laser physics, and erbium-doped fiber laser application.